A hybrid optimization approach to forecast automobile sales of China. (August 2017) - Gao, Junjie; Xie, Yanan; Gu, Feng; Xiao, Wei; Hu, Juanjuan; Yu, Wenlong
In this article, a novel Hybrid method based on particle swarm optimization and ant colony optimization (HPA) is proposed to forecast automobile sales of China. Proposed hybrid model integrating particle swarm optimization and ant colony optimization for estimation of Chinese automobile sales (HPAE) is the first model using aforementioned meta-heuristic techniques. HPA is developed for automobile sales forecasting using highway mileage, gross domestic product, automobile ownership, and consumer price index. HPAE is developed in two forms including both Linear (HPAEL) and Quadratic (HPAEQ). Then, in order to show the accuracy of the algorithm, a comparison is made with ant colony optimization and particle swarm optimization. The results show that mean absolute errors of the HPAE model are the best among them, and better-fit solutions are provided by quadratic form (HPAEQ) due to fluctuations of the influential indicators in China.